APLIKASI DATA TEKNIK PERALATAN DAN GANGGUAN GITET TASIKMALAYA - Sarmidi - (LPPM STMIK DCI, 2017)
This electrical energy is energy that is very important in human life because the human electrical energy becomes relatively easier to perform daily activities. Electrical energy to meet ever more increasing its use will require a continuous supply of electricity to meet the needs of the community. But the limited ability of electrical energy providers should also consider its ability to provide electrical energy, since every operating system power does not escape from the inevitable disruption. With increasing power consumption, the reliability of the electricity system needs it's own, especially on electrical power systems. Electrical equipment installed in the substation should be monitored for 24 hours by the operator and junior engineering assistant in each of the substation so that the reliability of the operating system reliability is maintained. To minimize disruption as early as may be required continuous monitoring equipment and the availability of equipment engineering data quickly and accurately, if at any time will be needed. in this case the writer intends to make a program / application that is able to facilitate the work of engineering data and data storage equipment in GITET TASIKMALAYA disorders with a better system and data processing dihasilkanpun be more accurate than the previous system were assessed to be less accurate and less orderly good. Keyword : GIGET, Facilitate, Engineering